Social and Personality Development in Childhood - Kata Zsófia Prém, Laura Kovács-Berényi; Raposa, Bernadett; Hámornik, Balázs Péter (2025)
Social and Personality Development in Childhood is a comprehensive and timely guide designed to bridge the gap between developmental psychology and legal practice. Developed in collaboration with the Ferenc Mádl Institute of Comparative Law and the Association for Children's Rights, this volume equips legal professionals, educators, and social workers with a profound understanding of the complex milestones involved in children's social and personality development.At the core of this book is the bio-psycho-social approach, a holistic framework emphasizing that a child's journey to adulthood is shaped by deeply interconnected biological, psychological, and social factors. By translating complex psychological theories into actionable knowledge, the book empowers professionals to make informed, child-centered decisions that truly serve the "best interests of the child," as guided by the UN Convention on the Rights of the Child.To provide a structured and highly accessible reading experience, the volume is divided into three distinct sections:• Children in the 21st Century: Explores the modern societal, digital, and cultural contexts impacting children today, providing a critical overview of current youth mental health challenges and psychological well-being.• Social and Emotional Considerations in Personality Development: Offers a deep dive into the major stages of emotional and cognitive growth, detailing the profound impacts of developmental trauma, the protective power of resilience, and the intricacies of the psychological assessment process.• Future Perspectives: Provides a forward-looking analysis of modern parenting dynamics and advocates for the vital implementation of trauma-informed educational and childcare systems.More than just a theoretical textbook, this work serves as an essential practical tool for effective advocacy and intervention. It champions the fundamental belief that integrating psychological insight into legal and social frameworks is essential—because a society's commitment to the holistic health and well-being of its children remains its most secure strategic investment in the future.